استرات جٌ اٌت الاتصال لدى مد رٌ ةٌ محافظة الغابات وتأث رٌها على الجمهور الخارج - زخسوز نجلاء سامية; بن سعيدي عائشة صفاء; د/د-نوعي عبد القادز (جامعة عمار ثليجي الاغواط, 2023)
ملخص الدراسة : تهدف الدراسة إلى التعرف على مدى مساهمت إستراتيجيات الاتصال في التأثير على الجهور الخارجي لدى ادارة حماية الغابات، وكذلك الكشف عن مدى مساهمة إستراتيجيات الاتصال من حيث الابلاغ عن أي مشكلة بالغابة، ومعرفة مدى مساهمة استراتجيات الاتصال من حيث اتباع تعليمات مديرية الغابات. ولبلوغ أهداف الدراسة قمنا بتصميم استبيان لجمع المعلومات اللازمة والإجابة على تساؤلات الدراسة التي احتوتها الاستمارة وقد اعتمدنا في دراستنا على المنهج الوصفي بهدف وصف الظاهرة وجمع أكبر عدد ممكن من المعلومات حول موضوع دراستنا، ومن أبرز النتاStudy summary: The study aims to identify the extent of the contribution of communication strategies in influencing the external public at the Forest Protection Department, as well as to reveal the extent of the contribution of communication strategies in terms of reporting any problem in the forest, and to know the extent of the contribution of communication strategies in terms of following the instructions of the Forestry Directorate. In order to achieve the objectives of the study, we designed a questionnaire to collect the necessary information and answer the questions of the study contained in the form. In our study, we relied on the descriptive approach in order to describe the phenomenon and collect the largest possible number of information on the subject of our study. Among the most prominent findings of our study are the following: 1. External communication and its strategies in the forest governorate of the wilaya of Laghouat (Aflo) is an exchange of information between the institution and its external audience, in addition to all communication activities directed to the external audience of the organization. 2. External communication in the forest governorate of Laghouat affects the achievement of the institution's goals in a high way, as the institution is interested in communicating information to the external environment. 3. One of the most important means adopted by the forest governorate of the wilaya of Laghouat in its communication with its external audience is the Internet. 4. Banners are among the most prominent strategies adopted in announcing the activities of the Foundation for the Preservation of Forests in the wilaya of Laghouat. 5. The Forest Preservation Institution of the state of Laghouat suffers from some difficulties represented by human difficulties, followed by organizational and finally financial difficulties. 6. One of the difficulties that faced the forest governorate of the state of Laghouat in communicating with members of the community is the lack of environmental awareness among citizens ئج التي توصلت اليها دراستنا ما يلي : 1. الاتصال الخارجي واستراتجياته في محافظة الغابات لولاية الأغواط بدلية(أفلو) هو عبارة عن تبادل المعلومات بين المؤسسة وجمهورها الخارجي إضافة إلى جميع أنشطة الاتصال الموجهة لجمهور المنظمة الخارجي . 2. يؤثر الاتصال الخارجي في محافظة الغابات لولاية الاغواط على تحقيق أهداف المؤسسة بشكل عالي إذ تهتم المؤسسة بإيصال المعلومات للمحيط الخارجي. 3. من أبرز الوسائل التي تعتمدها محافظة الغابات لولاية الاغواط في اتصالها بجمهورها الخارجي هي الانترنت . 4. تعد اللافتات من أبرز الاستراتيجيات المعتمدة في الإعلان عن نشاطات المؤسسة لولاية الاغواط. 5. تعاني مؤسسة محافظة الغابات لولاية الاغواط من بعض الصعوبات والمتمثلة في الصعوبات البشرية وتليها التنظيمية وأخيرا الصعوبات المادية . 6. من الصعوبات التي واجهت محافظة الغابات لولاية الاغواط في الاتصال بأفراد المجتمع قلة الوعي البيئي لدى المواطنين .